Sabotage in dynamic tournaments with heterogeneous contestants: Evidence from European football - Zhao, Y.; Zhang, H. (International Journal of Sports Science & Coaching, 2023)
This paper analyses how sabotage, measured as the number of fouls and yellow and red cards, is affected by the relative performance of and asymmetries between teams, determined based on score margin and the odds gap between one team and its opponent. By applying detailed controls for within-match dynamics and differences in team quality, we first observe that badly losing favourites are more willing than losing underdogs to increase their unsporting behaviour in heterogeneous contests. There are more yellow cards and fouls as the game progresses. We further find that most sabotage (yellow cards) can be observed when the (absolute) goal difference is equal to 1. Teams decrease their level of sabotage (fouls) by increasing the number of goals of lead or trail. In addition, weaker teams have an incentive to engage in more unfair and destructive strategies, such as committing more fouls, including those penalized with yellow cards. However, the incidence of red cards is not influenced by the score margin or strength gap.